Формирование опыта творческой деятельности студентов в образовательной среде - Волкодав, Татьяна Владимировна (International Dialogues on Education Journal, 2017)
The article examines the practical issues of the development of students’ creative potential based on the realization of KubSU students’ creative film projects. Creativity can be regarded as a production of insights, new ideas or products that result from defining a problem and solving it in a novel way within a particular socio-cultural context. Sensitivity and awareness of our time and place comes when we focus more on the here and now. Searching for the insights and new solutions requires the ability to apply creative strategies and be open to unexpected possibilities. In modern society that seeks the ‘right answer’ and tends to rely heavily on rational thought, abstract logic and deductive reasoning to solve problems, creative thinking tends to be underdeveloped in most of us. To accept the challenge of self-identity in the period of uncertainty, the educational environment can be adapted to foster the students’ creative potential by stimulating open-ended, divergent, inductive, non-linear and creative thinking.